The empirical validation of house energy rating (HER) software for lightweight housing in cool temperate climates - Dewsbury, Mark Andrew (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2015)
This book reports on the first empirical validation of "AccuRate," Australia's national benchmark software tool for house energy ratings. The validation was conducted by the University of Tasmania in collaboration with Forest and Wood Products Australia, the Australian Government, the CSIRO and industry partners. The study presented here describes the results of graphical and statistical analysis of variations observed between the measured and simulated data from three different test buildings in Launceston, Tasmania. It shows that, while the AccuRate software is well suited to modeling energy flows, there are discrepancies between the simulated and measured temperatures of the test buildings. Moreover, it highlights possible connections between the discrepancies in all zones and the outside air temperature, wind speed, global and diffuse solar radiation, and possibly the ground model. Beyond its contribution to further investigations into the ongoing improvement and calibration of the Australian NatHERS-supported AccuRate software, this book also meticulously describes the methodology used in conducting the research, which is expected to pave the way for further studies of this type.